Strange orbit - Simpson, Margaret, 1943- (State University of New York Press, 1995)
Fourteen-year-old Jessica is chosen to go the moon on the International Youth Space Trip, but the spaceship inexplicably misses its destination and sends the crew on a mysterious voyage through space, time, and the mind itself, transforming them all in the process.